2021
DOI: 10.3389/fsufs.2021.664103
|View full text |Cite
|
Sign up to set email alerts
|

Beyond CO2: Multiple Ecosystem Services From Ecologically Intensive Grazing Landscapes of South America

Abstract: Sustainability assessments to inform the design of multifunctional grazing landscapes need to look beyond greenhouse gas emissions to simultaneously embrace other social and environmental criteria. Here I briefly examine trade-offs and synergies between the productivity of graze-based livestock systems and the environment, and share a few generic guidelines to design pathways for the ecological intensification of livestock systems following agroecological principles. I draw from experience on livestock farming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Our meta-analysis revealed only a small difference in predicted CH 4 production between confinement and grazing systems, and no changes in CH 4 yield and CH 4 intensity ( Table 4 ). However, a fair comparison and evaluation of dairy management systems should also consider greenhouse gas emissions from crop production, transportation, and manure management, as well as ecosystem services provided by grazing dairies ( Fredeen et al, 2013 ; Tittonell, 2021 ), which was beyond the scope of our study. Nevertheless, results from studies that have compared the carbon footprint of grazing and confinement dairy systems are not consistent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our meta-analysis revealed only a small difference in predicted CH 4 production between confinement and grazing systems, and no changes in CH 4 yield and CH 4 intensity ( Table 4 ). However, a fair comparison and evaluation of dairy management systems should also consider greenhouse gas emissions from crop production, transportation, and manure management, as well as ecosystem services provided by grazing dairies ( Fredeen et al, 2013 ; Tittonell, 2021 ), which was beyond the scope of our study. Nevertheless, results from studies that have compared the carbon footprint of grazing and confinement dairy systems are not consistent.…”
Section: Resultsmentioning
confidence: 99%
“…Pasture-based systems are known to perform multiple ecosystem services including food production, climate regulation, pollination, nutrient cycling, and erosion control ( Sala et al, 2017 ; Tittonell, 2021 ), as well as use of marginal lands not suitable for tillage and crop production ( Wang et al, 2021 ). Grazing ruminants can also express their natural behaviors while on pasture ( Charlton et al, 2011 ), and previous research revealed that dairy cows were more motivated to go outside to graze than stay indoors and consume a total mixed ration (TMR) offered immediately after the afternoon milking ( von Keyserlingk et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the ecosystem services provided by rangelands, the provisioning services of forage and livestock production are the most widely recognized, but critical regulating, supporting, and cultural ecosystem services also exist. Despite their ecological and economic importance, rangelands continue to be undervalued (Vetter 2020; Tittonell 2021) and are frequently converted to alternative land uses with little regard for the associated loss of ecosystem services (Briske and Coppock 2023). This makes rangelands especially vulnerable to afforestation initiatives financed by C offset markets and supported by restoration and conservation programs.…”
Section: Program Magnitude Time Framementioning
confidence: 99%
“…The Campos are subtropical humid highly diverse native grasslands that foster extensive sheep and cattle production across the Pampa biome in Uruguay, southern Brazil, and center-eastern Argentina. These systems are currently facing the challenge of both increasing profitability and at the same time maintaining native grasslands as their main feed source in order to keep low system-wide costs ( Jaurena et al, 2021 ), be resilient against extreme climatic events ( Briske, 2017 ), and preserve the various valuable ecosystem services they provide ( Modernel et al, 2016 ; Tittonell, 2021 ).…”
Section: Introductionmentioning
confidence: 99%